2019
DOI: 10.1371/journal.pone.0224670
|View full text |Cite|
|
Sign up to set email alerts
|

Trends and predictors of mother-to-child transmission of HIV in an era of protocol changes: Findings from two large health facilities in North East Nigeria

Abstract: BackgroundResearch studies have demonstrated a reduction in the risk of mother-to-child transmission of HIV (MTCT) to less than 2%, or 5% in non-breastfeeding and breastfeeding populations, respectively, with antiretroviral interventions. However, the risk of MTCT in routine health-facility settings, where service delivery is usually sub-optimal needs monitoring.MethodWe conducted a retrospective review of data from 2008–2014, in two health facilities in Adamawa State, Nigeria. Descriptive statistics were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 22 publications
4
11
0
Order By: Relevance
“…Three studies involving 433 participants reported on the MTCT rate of HBV in mother–infant pair with HBV mono-infection confirmed using PCR technique. 35 37 The MTCT rate for HBV were reported to be 42.86% by Onakewhor et al, 35 51.6% by Eke et al, 36 and 72.0% by Olaleye et al 37 among newborns at birth. The results of our meta-analysis revealed that the overall MTCT rates for HBV mono-infections as seen in the three included studies that reported on HBV mono-infections was 55.49% (95% CI: 35.93%–75.04%; 433 participants; three studies, I 2 = 100%; p-value < 0.001) ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 97%
“…Three studies involving 433 participants reported on the MTCT rate of HBV in mother–infant pair with HBV mono-infection confirmed using PCR technique. 35 37 The MTCT rate for HBV were reported to be 42.86% by Onakewhor et al, 35 51.6% by Eke et al, 36 and 72.0% by Olaleye et al 37 among newborns at birth. The results of our meta-analysis revealed that the overall MTCT rates for HBV mono-infections as seen in the three included studies that reported on HBV mono-infections was 55.49% (95% CI: 35.93%–75.04%; 433 participants; three studies, I 2 = 100%; p-value < 0.001) ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 97%
“…Data published in a retrospective review did not specifically identify the protocols used in Nigeria as being Option B+. Regardless, a marked decrease in MTCT from 2008 (14.3%) to 2014 (4.9%) was reported 54 . More recent data from the north central zone reported an MTCT rate of 11.4% in infants at age 20 months or older.…”
Section: Discussionmentioning
confidence: 93%
“…Regardless, a marked decrease in MTCT from 2008 (14.3%) to 2014 (4.9%) was reported. 54 More recent data from the north central zone reported an MTCT rate of 11.4% in infants at age 20 months or older. Only 54.5% of mothers received ART medication prior to pregnancy.…”
Section: Challenges Of Implementationmentioning
confidence: 96%
“…The current discussions are on mapping current epidemiology, administration of antiretroviral therapy and the prevention of mother-to-child-transmission of HIV. For instance, there have been varying current discussions on trends, predictors, spatial patterns, knowledge and the reduction of mother-to-child transmission of HIV in Nigeria [46][47][48][49][50]. Often, the first response to an epidemic is to characterize the disease followed by diagnosis and possible means of amelioration/cure.…”
Section: Discussionmentioning
confidence: 99%